Tin coating requirements in fish cans - Vijayan, P.K., Balachandran, K.K. and (Fishery Technology, 2021)
Prawn, crab and clam meat were processed in experimental ca s having reduced internal tin coating of 5.6 GSM. Conventional cans having 11.2 GSM tin coating were used as control. Results showed that experimental cans behaved normally when used for canning prawns, provided the lacquer film was perfect with no exposure of metal. When there was a discontinuity in lacquer film exposing the metal blackening took place in such areas. Areas subjected to severe strains like the lock seam side and expansion rings on can ends were found to be more prone to blackening. Experimental cans were found unsuitable for canning crab meat or clam meat because in both cases the can wall as well as the contents underwent discoloration, in all cases.